Effectiveness of the Ad26.COV2.S (Johnson & Johnson) Coronavirus Disease 2019 (COVID-19) Vaccine for Preventing COVID-19 Hospitalizations and Progression to High Disease Severity in the United States . (8th June 2022) - Lewis, Nathaniel M; Self, Wesley H; Gaglani, Manjusha; Ginde, Adit A; Douin, David J; Keipp Talbot, H; Casey, Jonathan D; Mohr, Nicholas M; Zepeski, Anne; Ghamande, Shekhar A; McNeal, Tresa A; Shapiro, Nathan I; et al.
Abstract: Background . Adults in the United States (US) began receiving the adenovirus vector coronavirus disease 2019 (COVID-19) vaccine, Ad26.COV2.S (Johnson & Johnson [Janssen]), in February 2021. We evaluated Ad26.COV2.S vaccine effectiveness (VE) against COVID-19 hospitalization and high disease severity during the first 10 months of its use. Methods . In a multicenter case-control analysis of US adults (≥18 years) hospitalized 11 March to 15 December 2021, we estimated VE against susceptibility to COVID-19 hospitalization (VEs), comparing odds of prior vaccination with a single dose Ad26.COV2.S vaccine between hospitalized cases with COVID-19 and controls without COVID-19. Among hospitalized patients with COVID-19, we estimated VE against disease progression (VEp) to death or invasive mechanical ventilation (IMV), comparing odds of prior vaccination between patients with and without progression. Results . After excluding patients receiving mRNA vaccines, among 3979 COVID-19 case-patients (5% vaccinated with Ad26.COV2.S) and 2229 controls (13% vaccinated with Ad26.COV2.S), VEs of Ad26.COV2.S against COVID-19 hospitalization was 70% (95% confidence interval [CI]: 63–75%) overall, including 55% (29–72%) among immunocompromised patients, and 72% (64–77%) among immunocompetent patients, for whom VEs was similar at 14–90 days (73% [59–82%]), 91–180 days (71% [60–80%]), and 181–274 days (70% [54–81%]) postvaccination. Among hospitalized COVID-19 case-patients, VEp was 46% (18–65%) among immunocompetent patients. Conclusions . The Ad26.COV2.S COVID-19 vaccine reduced the risk of COVID-19 hospitalization by 72% among immunocompetent adults without waning through 6 months postvaccination. After hospitalization for COVID-19, vaccinated immunocompetent patients were less likely to require IMV or die compared to unvaccinated immunocompetent patients. Abstract : In a multicenter case-control analysis of hospitalized US adults (≥18 years), the viral vector coronavirus disease 2019 (COVID-19) vaccine, Ad26.COV2.S, reduced risk of hospitalization with COVID-19 by 70%, consistent up to >180 days postvaccination and across periods of different variant predominance.